2013
DOI: 10.1007/s11948-013-9499-3
|View full text |Cite
|
Sign up to set email alerts
|

The Human Right to Water: The Importance of Domestic and Productive Water Rights

Abstract: The United Nations (UN) Universal Declaration of Human Rights engenders important state commitments to respect, fulfill, and protect a broad range of socio-economic rights. In 2010, a milestone was reached when the UN General Assembly recognized the human right to safe and clean drinking water and sanitation. However, water plays an important role in realizing other human rights such as the right to food and livelihoods, and in realizing the Convention on the Elimination of All Forms of Discrimination against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 17 publications
(24 reference statements)
1
43
0
3
Order By: Relevance
“…If there is a continuing trend, exemplified by the right to water as presented by Meier, et al (2014 ) and Hall et al (2013), to develop new or derivative human rights in a wide range of scientific and technological fields, the engagement of scientists and engineers, in partnership with human rights specialists, will be essential to translate normative pronouncements into "enhanced opportunities for rights-based ... policy" and "actual interventions" (Hall et al, 2013). This special section of Science and Engineering Ethics on technology, engineering and human rights is a good beginning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is a continuing trend, exemplified by the right to water as presented by Meier, et al (2014 ) and Hall et al (2013), to develop new or derivative human rights in a wide range of scientific and technological fields, the engagement of scientists and engineers, in partnership with human rights specialists, will be essential to translate normative pronouncements into "enhanced opportunities for rights-based ... policy" and "actual interventions" (Hall et al, 2013). This special section of Science and Engineering Ethics on technology, engineering and human rights is a good beginning.…”
Section: Resultsmentioning
confidence: 99%
“…Both assume the value of expanding the corpus of international human rights. While Meier et al are concerned about translating this right from formal international and national pronouncements into practical action at the local level, Hall et al suggest "adopting a more holistic interpretation of existing international law on the human right to water" (Hall et al 2013). …”
Section: The Right To Water and The Human Rights Norm-creating Processmentioning
confidence: 99%
“…The non-legal literature critiques the narrow formulation of the HRW which affects the realisation of HRS norms especially for people relying on various wet sanitation systems (Joshi et al, 2011;Hall, van Koppen & van Houweling, 2014); analyses the central role of knowledge in the re-production of the urban waterscape, including wastewater (for instance, Bakker, 2003;Castro, 2004;Kaika, 2003;Karpouzoglou & Zimmer, 2016;Swyngedouw, Kaïka & Castro, 2002); assesses sanitation governance processes and the motivations and accountability of key actors (Abeysuriya, Mitchell & White, 2007;Giles, 2012;Meier et al, 2014), even using human rights standards (Galvin, 2015); and proffers quantitative and qualitative indicators for measuring access levels (Bain et al, 2014;Baum et al, 2013;Ensink, et al, 2008;Ensink et al, 2015;Irish et al, 2013;Kvarnström et al, 2011). The nonlegal literature however does not sufficiently address the HRS norms beyond a cursory consideration at best but has instead focused largely on the technological and economic aspects of sanitation services (Obani & Gupta, 2016 analyses the coverage of the HRS in the legal and non-legal literature in detail).…”
Section: Incoherence Between Legal and Non-legal Research On The Humamentioning
confidence: 99%
“…For example, Hall et al ( 2013 ) found that even at consumption levels of 20 l per capita per day, half of the households used these quantities for domestic and productive uses. In mountainous areas with free gravity energy in Colombia, the proportion of households using pipes for multiple uses is 82-98 % in three rural areas, but only just below 50 % in two urban areas (Van Koppen et al 2009 ).…”
Section: Rights-based Water Services For Productive and Multiple Watementioning
confidence: 99%
“…Currently, service levels for water supplies delivered near or at homesteads are 20-50 l per capita per day, supposedly to meet personal and domestic needs (and sanitation) only. This should be raised to 50-100 l per capita per day in order to also enable basic productive uses (Hall et al 2013 ;Van Koppen et al 2014a ). Unlike irrigation development that tends to disproportionately favour those with more land, multiple-use water services to homesteads benefi t everybody, including the land-poor and landless, childheaded households, the sick and disabled.…”
Section: Rights-based Water Services For Productive and Multiple Watementioning
confidence: 99%